Crime policy in America: laws, institutions, and programs - Shahidullah, Shahid M. (Univ. Press of America, 2008)
"This book is a systematic examination of the nature of America's crime and criminal justice system as defined by its policy-makers at different times and in disparate contexts of social and political realities. By examining legislative documents and court cases and analyzing federal and state policy developments in such areas as drug crimes, juvenile crimes, sex crimes, and cyber crimes, this book provides a historically embedded and policy relevant understanding of how America's system of criminal justice was born, how it has grown, and where it is going."--Jacket